Prevention of Transmission of TB Disease with the Approach of Neuman System Model in Kawangu Community Health Center East Sumba Regency Indonesia - Gunawan, Yosephina Elizabeth Sumartini (Jurusan Keperawatan FIKES UNSOED, 2018)
Introduction: Family empowerment needs to be done to improve the knowledge, awareness and willingness of the family in its efforts to prevent the transmission of TB disease. This study aims to explainÃ‚Â the influence of the approach NeumanÃ¢â‚¬â„¢s System Model to the prevention of transmission of TB. Methods: The design of this study is quasy experimental with the approach of the pre-post mehod with control group design. Sample research as many as 32 of the family, namely the 16 families in the treatment group and 16 families in the control group were determined purposively. Results: there is significant effect of treatment against the level of knowledge of the treatment group with z by -2.432 and significant valueÃ‚Â of 0.001 and a significant influence of the treatment given to the prevention control groups with z value -2.039 and significant value of 0.041. Different test showed significant difference on the knowledge of the control group ang the treatment of 0.039 and z values -2.066 and there is a significant difference in prevention efforts of the control group and the treatment of 0.000 with a value of z -4.642. Conclusions: the approach of NeumanÃ¢â‚¬â„¢s System Model performed in the treatment group have a significant influence on the increased knowledge and prevention of transmission of TB disease conducted by the family.